PENGARUH MOTIVASI TERHADAP PRESTASI (Studi Kasus pada Siswa SMK PGRI Sutojayan Blitar) - Nurul Farida (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2016)
This study is aimed to see the effect of motivation to students’ achievement of students of SMK PGRI Sutojayan Blitar.  The study used double liniear regression on Y = a + b1X1 + b2X2 b3X3 + e. The subject of the study was the X graders of SMK PGRI Sutojayan.  Data were collected using test and questionnaire. Analysis of regression identifies Y = 0,942, X1=0,092, X2=0,685, X3=0,811, implying that there is high significant relationship between learning motivation and learning achievement.